El narco: inside Mexico's criminal insurgency - Grillo, Ioan (Bloomsbury Press, 2011)
"The world has watched stunned at the bloodshed in Mexico. Forty thousand murdered since 2006; police chiefs shot within hours of taking office; mass graves comparable to those of civil wars; car bombs shattering storefronts; headless corpses heaped in town squares. And it is all because a few Americans are getting high. Or is it? The United States throws Black Hawk helicopters, DEA assistance, and money at the problem. But in secret, Washington is confused and divided about what to do. Who are these mysterious figures tearing Mexico apart, they wonder. What is El Narco? El Narco draws the first definitive portrait of Mexico's cartels and how they have radically transformed in the past decade. El Narco is not a gang; it is a movement and an industry drawing in hundreds of thousands, from bullet-ridden barrios to marijuana-covered mountains. The conflict spawned by El Narco has given rise to paramilitary death squads enlisting tens of thousands of men-at-arms ready to do battle from Guatemala to the Texas border (and sometimes beyond.) Journalist Ioan Grillo has spent a decade in Mexico covering the drug war from the front lines. This piercing book joins testimonies from inside the cartels with firsthand dispatches and unsparing analysis. The devastation may be south of the Rio Grande, El Narco shows, but the United States is very much a part of the battleground."--Book jacket